Development Of Tio2-Zno Photocatalyst Incorporated Lldpe For Antimicrobial Application - Khor, Yong Ling (Universiti Sains Malaysia, 2017)
In recent decades, the rapid growth of pathogens are rising human concern about the susceptible attack of harmful microorganisms in especially human health related sectors including hospitals and dental equipment, food packaging and storage. Coupled TiO2/ZnO photocatalysts was well known with its antimicrobial properties. However, the study on the antimicrobial activity of TiO2/ZnO incorporated polymers was not investigated comprehensively. Hence, this work aims to develop TiO2/ZnO photocatalyst incorporated LLDPE for antimicrobial application. The TiO2/ZnO photocatalyst was prepared through sol-gel with TTIP and ZAD as precursors in ethanol solution followed by calcination for 2 hours at 500 oC. It was found that 25TiO2/75ZnO has the highest photodegradation efficiency of 95.59 % in degrading of 3ppm of methylene blue under 3 hours of sunlight irradiation. Based on PL results, 25TiO2/75ZnO has the highest emission intensity in blue range (465-485 nm) and yellow-orange range (570-650 nm) indicating the most structural defects present which enhanced the photocatalytic activity. The TiO2/ZnO photocatalyst incorporated LLDPE films fabricated by solution casting using 1,2-Dichlorobenzene at 75 oC and oven dried at 80oC have degree of crystallinity (<30%) adequate for antimicrobial agent release and higher tensile strength and young modulus compared to the pure LLDPE film. Lastly, under the protocol of ASTM E2149, the higher the wt% loading of 25TiO2/75ZnO photocatalyst in the LLDPE composite film, the more percentage of reduction in S. aureus. The highest antimicrobial activity was observed with the 10 wt% 25TiO2/75ZnO loaded LLDPE with 100% reduction of S. aureus within 24 hours.